2000
DOI: 10.1038/sj.leu.2401715
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to apoptosis in human AML blasts: the role of differentiation-induced perturbations of cell-cycle checkpoints

Abstract: Alterations in the response of leukaemic cells to apoptosisinducing stimuli may account for resistance to chemotherapy and treatment failure, either by disruption of the apoptotic pathway itself or by altered DNA repair; quiescent cells and those with disrupted cell-cycle checkpoints may also display decreased apoptosis. Quiescence can be induced by the differentiation of myeloid cells, and this led us to investigate whether the modulation of drug-induced apoptosis associated with differentiation might be a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…34 Although apoptosis-resistant pathways during differentiation of leukemic cells are poorly understood, there is evidence that members of the Bcl-2 family are involved in the regulation of these processes. For example, Mcl-1 and A1, members of the Bcl-2 family, are required to prevent apoptosis during differentiation of leukemic U937 or NB4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although apoptosis-resistant pathways during differentiation of leukemic cells are poorly understood, there is evidence that members of the Bcl-2 family are involved in the regulation of these processes. For example, Mcl-1 and A1, members of the Bcl-2 family, are required to prevent apoptosis during differentiation of leukemic U937 or NB4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in HL60 or U937 cell lines, resistance to drug-induced apoptosis increases with greater duration following incubation with retinoic acid or vitamin D3. 39,40 This protective effect correlates with the degree of G0/ G1 accumulation but is independent of differentiation status or Bcl 2 expression levels.…”
Section: Figurementioning
confidence: 99%
“…1,2 The Ras/Raf/MEK/ERK pathway is known to control cell proliferation and cell survival, two activities that have a direct impact on tumor promotion and progression. 3,4 We have previously reported that ERK is constitutively activated in more than 50% of primary AMLs but not in normal CD34 þ progenitors 5 and that constitutive ERK activation is an independent prognostic factor for survival in AML (Kornblau et al, Blood 2001; 98: 716a).…”
Section: Introductionmentioning
confidence: 99%